2018
DOI: 10.14499/indonesianjcanchemoprev9iss1pp32-40
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cytotoxicity and Apoptosis Induction of Doxorubicin by Brazilein Containing Fraction of Secang (Caesalpinia sappan L.) on T47D Cells

Abstract: Combination chemotherapy (co-chemotherapy) is a recent strategy to reduce the toxicity effect and increase the effectivity of chemotherapeutic agent, such as Doxorubicin (Dox). Caesalpinia sappan L. are potential to be developed as co-chemoterapeutic agents due to its strong cytotoxicity toward several breast cancer cells. The purpose of this research is to observe the cytotoxicity of Brazilein containing fraction (BCF) in single and its combination with doxorubicin on T47D cells. BCF was obtained by fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Fraction-9 also exhibits a higher cytotoxic activity compared to the cytotoxic activity of ethyl acetate fraction reported on HeLa, MCF-7/Moc, MCF-7/Her2, and T47D cancer cells, where the range of IC50 were 40 -65μg/mL. [17][18][19] Investigation on anti-cancer activity of purified brazilin showed a potential anti-cancer activity of brazilin. Kim et al reported high cytotoxic activity of brazilin on MM cells (U266 and MM1s), leukemia cell line (K562) with the range of IC50 10-80μM.…”
Section: Discussionmentioning
confidence: 90%
“…Fraction-9 also exhibits a higher cytotoxic activity compared to the cytotoxic activity of ethyl acetate fraction reported on HeLa, MCF-7/Moc, MCF-7/Her2, and T47D cancer cells, where the range of IC50 were 40 -65μg/mL. [17][18][19] Investigation on anti-cancer activity of purified brazilin showed a potential anti-cancer activity of brazilin. Kim et al reported high cytotoxic activity of brazilin on MM cells (U266 and MM1s), leukemia cell line (K562) with the range of IC50 10-80μM.…”
Section: Discussionmentioning
confidence: 90%
“…Dox was expected to have an IC 50 value in less than 1 µM, as reported in its activities against other cancer cell lines. (15,27) Co-treatment with Dox is expected to increase the effectiveness of Dox, especially in dealing with colon cancer, because so far, several colon cancer therapy regimens have not been able to overcome the growing problem of resistance to colon cancer. (18,28) Dox is not currently an option for colon cancer therapy because Dox also has resistance problems and side effects that are difficult to avoid and have stability problems for oral use.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of Be in cell cycle progression seems to be typical for various cancer cells (11,23), which is generally continue to occur apoptosis (15). However, the effect of cell cycle arrest of co-treatment of Be and Dox on WiDr cells does not appear to be related to apoptotic induction.…”
Section: Amentioning
confidence: 96%
See 1 more Smart Citation
“…The success story of Paclitaxel from Taxus brevifolia as an anticancer drug on clinical trial induces researchers discovering natural products or its metabolites as novel chemopreventive agents. Several Indonesian natural products such as Caesalpinia sappan, Cinnamomum burmanii, and Nerium indicum have been Submitted: September 13, 2019 Revised: November 11, 2019 Accepted: November 11, 2019 *Corresponding author: desakgedesa@gmail.com explored their distinct chemopreventive mechanism on cancer cell (Larasati, et al, 2014;Lestari, et al, 2017;Utomo, et al, 2018). However, the lack of identification about the secondary metabolite contribute on its chemopreventive activity impacts on Indonesian Journal of Cancer Chemoprevention, October 2019 ISSN: 2088-0197 e-ISSN: 2355-8989 the bias standard for the application of certain natural products.…”
Section: Introductionmentioning
confidence: 99%